1990
DOI: 10.1111/j.1095-8312.1990.tb00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the distribution of chromosomal races of Mus musculus domesticus Rutty in Europe

Abstract: Robertsonian (Rb) translocation is a common chromosomal rearrangement in the house mouse. In free-living populations, 79 fusions with different combinations of chromosomes 1 to 18 have been found in some 45 populations. An updated list of these fusions is presented and analysed in order to reveal the possible processes by which the fusions spread within or among populations. A widespread hypothesis is that when two populations share the same fusion, it can be assumed that they have a common ancestor. This can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
11

Year Published

1991
1991
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 18 publications
1
48
0
11
Order By: Relevance
“…An experimental introduction of Rb mice in a karyotypically normal population has shown that Rb chromosomes can spread very rapidly in a population even though heterozygotes for three Rb metacentrics must have occurred (Berry et a!., 1990). According to his phylogenetic study of Rb populations in Europe, Bauchau (1990) suggests that most of the Robertsonian populations have non-independent origins and that chromosomal flow between these populations is an important process, contrary to what has been understood until now (see also Corti et a!., 1986;Winking eta! 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An experimental introduction of Rb mice in a karyotypically normal population has shown that Rb chromosomes can spread very rapidly in a population even though heterozygotes for three Rb metacentrics must have occurred (Berry et a!., 1990). According to his phylogenetic study of Rb populations in Europe, Bauchau (1990) suggests that most of the Robertsonian populations have non-independent origins and that chromosomal flow between these populations is an important process, contrary to what has been understood until now (see also Corti et a!., 1986;Winking eta! 1988).…”
Section: Discussionmentioning
confidence: 99%
“…However, these fusions are widely distributed among natural populations of Mus musculus domesticus in Western Europe and North Africa (Winking et a!., 1988;Bauchau, 1990). We are thus confronted with a paradox.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the overall distribution of metacentric races in M. m. domesticus, there is a concentration of such races in high altitude and coastal regions within Europe (Bauchau, 1990;Searle er at., 1990). One would expect particularly small populations in such areas, which may promote fixation of new chromosomal rearrangements (Lande, 1979).…”
Section: Association Of Races With Geographic Terrainmentioning
confidence: 99%
“…However, deviation from this standard complement has been documented in various parts of the range of the west European subspecies Mus musculus domesticus (Bauchau, 1990). Here we consider the substantial chromosomal variation in the extreme northern part of mainland Scotland, first discovered by Adolph & Klein (1981) and Brooker (1982).…”
Section: Introductionmentioning
confidence: 99%